Intraoperative Neural Monitoring in Endoscopic Thyroidectomy Via Bilateral Areola Approach. Issue 5 (October 2018) - Zhang, Daqi; Fu, Qingfeng; Dionigi, Gianlorenzo; Wang, Tie; Xin, Jingwei; Zhang, Jiao; Xue, Gaofeng; Li, Hongbo; Sun, Hui
Abstract : Objective: The aim of this report was dual: (a) to describe the step by step standardized intraoperative neural monitoring (IONM) procedure for recurrent laryngeal nerve (RLN) and external branch of the superior laryngeal nerve focusing on percutaneous IONM method, and (b) evaluation and outcomes of intermittent IONM in 237 endoscopic thyroidectomy via bilateral areolar approach cases. Materials and Methods: A 10-mm curved incision is made along the margin of the right areola at the 2 to 4 o'clock position for the 30-degree endoscope. Bilaterally 5-mm incisions are required on the edges of the areola at the 11 to 12 o'clock positions as accessory operating ports. Ball-tip, monopolar, single-use, standard stimulating probe with a 10-cm handle and 9-cm shaft is adopted percutaneously for IONM. As reference, on the dominant thyroid lesion side, a 0.5-cm circle is drawn with the center at the intersection of a line 2-cm lateral to the anterior median line and a line 2-cm above the line connecting the bilateral clavicular heads. After ensuring with ultrasonography that no vessels are within the puncture passage, the skin is pierced with an 18-G syringe needle. After withdrawing the needle, the probe is carefully inserted through the tract. IONM is performed according to standards of equipment set up, anesthesia, tube positioning verification tests, and electromyography determinations. Results: A total of 277 nerves at risk were favorably monitored with percutaneous probe stimulation. RLN, vagus nerve, and external branch of the superior laryngeal nerve were successfully determined. There were no instances of IONM malfunction, equipment displacement, or interference with the other endoscopic instruments. IONM probe insertion incision determined no scarring or morbidity in the neck. The incidence of RLN monolateral temporary palsy was 6%. Conclusions: Standardized monitoring in endoscopic thyroidectomy via bilateral areolar approach is feasible. IONM was implemented by means of percutaneous stimulating probe. Abstract : Supplemental Digital Content is available in the text.